Intraspecific variation in the skull morphology of the black caiman Melanosuchus niger (Alligatoridae, Caimaninae). (19th August 2013) - Foth, Christian; Bona, Paula; Desojo, Julia B.
Abstract Melanosuchus niger is a caimanine alligatorid widely distributed in the northern region of South America. This species has been the focus of several ecological, genetic and morphological studies. However, morphological studies have generally been limited to examination of interspecific variation among extant species of South American crocodylians. Here, we present the first study of intraspecific variation in the skull of M. niger using a two‐dimensional geometric morphometric approach. The crania of 52 sexed individuals varying in size were analysed to quantify shape variation and to assign observed shape changes to different types of intraspecific variation, that is, ontogenetic variation and sexual dimorphism. Most of the variation in this species is ontogenetic variation in snout length, skull depth, orbit size and the width of the postorbital region. These changes are correlated with bite force performance and probably dietary changes. However, a comparison with previous functional studies reveals that functional adaptations during ontogeny seem to be primarily restricted to the postrostral region, whereas rostral shape changes are more related to dietary shifts. Furthermore, the skulls of M. niger exhibit a sexual dimorphism, which is primarily size‐related. The presence of non‐size‐related sexual dimorphism has to be tested in future examinations.